2018
DOI: 10.1002/cnma.201800342
|View full text |Cite
|
Sign up to set email alerts
|

Cold Sintering of a Covalently Bonded MoS2/Graphite Composite as a High Capacity Li–Ion Electrode

Abstract: ABSTRACT. A cold sintering approach is demonstrated to fabricate highly dense electrochemically active MoS2/graphite (MG) composites with 88% relative density at an extremely low processing temperature of 140 °C. The process provides a pathway to sinter covalently bonded materials effectively to produce either dense or near dense pellets and/or thick films. Composites that include up to 20 wt% graphite, as well as a Li‐ionic solid electrolyte (lithium aluminum germanium phosphate) could be easily integrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In its usual form, cold sintering is characterized by the wetting of a powder followed by uniaxial pressing inside a heated die above the boiling temperature of the wetting solvent (typically aqueous). , In this manner, we have successfully applied cold sintering to the cathodes (MoS 2 , V 2 O 5 , and LiFePO 4 , ), an anode (Li 4 Ti 5 O 12 ), and a NASICON-type solid-state electrolyte (Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ) for lithium-ion batteries, primarily with low-temperature aqueous solvents. In densifying the Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 electrolyte, however, we needed to introduce a conductive salt additive to improve the conductivity to high values (>10 –4 S/cm).…”
Section: Introductionmentioning
confidence: 99%
“…In its usual form, cold sintering is characterized by the wetting of a powder followed by uniaxial pressing inside a heated die above the boiling temperature of the wetting solvent (typically aqueous). , In this manner, we have successfully applied cold sintering to the cathodes (MoS 2 , V 2 O 5 , and LiFePO 4 , ), an anode (Li 4 Ti 5 O 12 ), and a NASICON-type solid-state electrolyte (Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ) for lithium-ion batteries, primarily with low-temperature aqueous solvents. In densifying the Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 electrolyte, however, we needed to introduce a conductive salt additive to improve the conductivity to high values (>10 –4 S/cm).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that by adjusting the carbon nano fiber loading, the electrical conductivity and volumetric capacity was increased. CS of a covalently bonded (within the S-Mo-S layers) MoS 2 /graphite composite for use as a high capacity Li-Ion electrode was demonstrated, with fabrication of highly dense electrochemically active MoS 2 /graphite composites achieved with a relative density of 88%, using processing conditions of 140 °C, 520 MPa for 60 min [72]. The specific capacity of the composite electrode was ∼950 mAh g -1 at 0.1 A g -1 .…”
Section: Cold Sintering Process (Randall's Method)mentioning
confidence: 99%
“…[21,22] CSP has been shown to successfully densify a large range of materials, including ferroelectrics, microwave dielectrics, battery materials and semiconductors. [15,18,[23][24][25][26][27] However, the focus has been almost exclusively on oxides. To date, the only published application of CSP to a chalcogenide has been on MoS2/graphite composites.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To date, the only published application of CSP to a chalcogenide has been on MoS2/graphite composites. [15] In this work, ammonium molybdate tetrahydrate and thiourea were used instead of water as the liquid sintering aid, and 88% relative density was achieved by processing at 140 °C and 520 MPa for 60 mins. Attempts at CSP with water led to low relative density (~60%) due to the hydrophobic nature of MoS2 and graphite.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation